Evaluasi Implementasi Audit Kasus Stunting (AKS) Dalam Rangka Percepatan Penurunan Stunting di Jawa Timur - Fanani, Abdul Fatah; Hazna Safira, Ulfia; Rosyadi Hamid, Imron (Journal of Governance Innovation, 2025)
Stunting Case Audit (AKS) is a strategic intervention under the national policy to accelerate stunting reduction in Indonesia. Its implementation at the regional level requires comprehensive evaluation. This study aims to assess the implementation of AKS in East Java Province based on the perspectives of implementers at various levels of government. A descriptive quantitative approach was employed, involving 743 respondents comprising members of Village/Kelurahan TPPS, Sub-district TPPS, District/City TPPS, Technical Teams, Expert Teams, and the Stunting Task Force. Data were collected through an online questionnaire and analyzed using descriptive statistics with the assistance of SPSS. The evaluation was guided by the Input-Process-Output model and the "5 PASTI" framework. The study found that most regions had established regulations and institutional structures for AKS. The level of support from the Stunting Reduction Acceleration Teams (TPPS) at all levels was rated high, and the overall quality of AKS implementation was considered good. However, gaps were identified in the availability and understanding of the AKS pocketbook, inconsistency in auditee selection, and uneven follow-up of AKS results. Most respondents acknowledged that AKS is highly beneficial and should be continued. The implementation of AKS in East Java has been fairly effective, though it requires strengthening in technical understanding, dissemination of guidelines, and utilization of audit results in policymaking. Recommendations focus on enhancing implementers’ capacity, optimizing interventions, and expanding multisectoral funding. Keywords: Stunting, Stunting Case Audit, Policy Evaluation, Stunting Reduction Acceleration.